PENINGKATAN KUALITAS REAR DERAILLEUR HANGER PADA SEPEDA MULTI GEAR MELALUI PENAMBAHAN UNSUR MAGNESIUM - Rama, Rama Wijaya; Firdaus; Taufikurahman (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Rear derailleur is one of the components on a bicycle that functions to replace or change gears/speed by moving the bicycle chain from one wheel to another. In use, the rear derailleur requires an additional component to connect the rear derailleur to the bicycle frame, namely the rear derailleur hanger. Where the rear derailleur hanger is made of aluminum. In its application, the rear derailleur hanger often experiences damage caused by shock loading and breaks due to the collisions that occur. With the squzee casting method, the smelted material is put into the mold cavity which is then pressed using a hydraulic tool when the material is almost frozen with variations in the addition of the percentage of elemental magnesium by 2%, 4% and 5% with a pressure statement of 70 MPa and the melting temperature reaches a point of 660ÌŠ C. In the results obtained the average value of the Impact price is at a composition of 2% magnesium by 0.0357 J/mm2, at a composition of 4% by 0.0951 J /mm2, and 6% composition of 0.0594 J/mm2, it can be observed that the highest addition was produced at a percentage addition of 4% and decreased in value at a percentage of 6%. From the results of the study showed an increase in the value of the value of the raw material that is equal to 0.0178 J/mm2. Â